The dating charade : a novel - Ferguson, Melissa (Assistant professor) (Thomas Nelson, 2019)
Cassie Everson is an expert at escaping bad first dates. And, after years of meeting, greeting, and running from the men who try to woo her, Cassie is almost ready to retire her hopes for a husband<U+2014>and children<U+2014>altogether. But fate has other plans, and Cassie<U+2019>s online dating profile catches the eye of firefighter Jett Bentley. In Jett<U+2019>s memory, Cassie Everson is the unreachable girl-of-legend from their high school days. Nervously, he messages her, setting off a chain of events that forces a reluctant Cassie back into the dating game. No one is more surprised than Cassie when her first date with Jett is a knockout. But when they both go home and find three children dropped in their laps<U+2014>each<U+2014>they independently decide to do the right and mature thing: hide the kids from each other while sorting it all out. What could go wrong?